2003
DOI: 10.1007/s00383-003-1016-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effect of a high fat diet on lipid absorption and fatty acid transport in a rat model of short bowel syndrome

Abstract: Long chain fatty acids (LCFAs) appear to be powerful stimulants for small bowel adaptation in patients with short bowel syndrome (SBS). However, the dietary lipid content may alter intestinal lipid transport. The aim of this study was to investigate the effects of a high fat diet (HFD) on in vivo lipid absorption and molecular and cellular mechanisms of LCFAs uptake by the remaining bowel. Male Sprague-Dawley rats (240-280) were randomly assigned to one of three groups: sham rats fed normal chow (sham-NC), SBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…This study raises important questions regarding the dietary management of infants with SBS. Overall, research evidence from this and previous studies shows that high fat diets and diets high in LCPUFA are most beneficial in cases of SBS (4,5,(7)(8)(9)(10)(11) and that low-fat diets impair postresection intestinal adaptation (6), despite that these findings are paradoxical to current wide-spread clinical practice. Infants with SBS are often given elemental formula containing less fat than human breast milk, having considerably high medium-chain fatty acids, and being dominated by n-6 PUFA.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This study raises important questions regarding the dietary management of infants with SBS. Overall, research evidence from this and previous studies shows that high fat diets and diets high in LCPUFA are most beneficial in cases of SBS (4,5,(7)(8)(9)(10)(11) and that low-fat diets impair postresection intestinal adaptation (6), despite that these findings are paradoxical to current wide-spread clinical practice. Infants with SBS are often given elemental formula containing less fat than human breast milk, having considerably high medium-chain fatty acids, and being dominated by n-6 PUFA.…”
Section: Discussionmentioning
confidence: 58%
“…Enteral fats seem to be the most trophic macronutrients in inducing adaptation (3)(4)(5). High fat diets (5)(6)(7)(8) and diets enriched with long chain fatty acids (9,10) have been shown to be more effective, and especially, diets rich in long chain polyunsaturated fatty acids (LCPUFA) are the most beneficial in stimulating mucosal adaptation (4,11). Fish oil (FO) is a main source of n-3 LCPUFA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA).…”
mentioning
confidence: 99%
“…In non-operated, non-stressed animal, total food intake is 20-25 g/rat/day, total protein intake is about 6 g/rat/day, and total energy intake is 100 kcal/rat/day [22]. We do not believe that an additional 300 mg/rat/day of protein (vs 6 g of total protein) as well as additional energy of 1.2 kcal/rat (vs total 100 kcal/rat/day) may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggested that apical membrane proteins on enterocytes may facilitate FA transfer and direct the FA to the appropriate metabolic sites. Regulatory effects of protein-mediated transport were also suggested by the adaptive changes in brush-border membrane FA uptake in response to environmental challenges (208, 221) and by the variability, possibly genetically determined, of FA uptake by intestinal segments from various mice strains (103). In the following discussion we will try to integrate the data related to intestinal FA transport into a working model that could provide a starting point for further work.…”
Section: Fatty Acid and Sterol Traffickingmentioning
confidence: 99%